Journal of Human Sport and Exercise - 2019 - Spring Conferences of Sports Science 2019
DOI: 10.14198/jhse.2019.14.proc4.60
|View full text |Cite
|
Sign up to set email alerts
|

Physical-technical conditions, coaching and nutrition: An integrated approach to promote cohesion in sports team

Abstract: The aim was verified that the level of cohesion of a sports group is conditioned by numerous variables, which affect the athletes performance and lead to difficulties in adults relationships. The sample physical-technical and nutritional conditions and the help for the cohesion of a technique such as coaching were evaluated. Coaching can understand as the process in which individuals, mostly athletes, supported for their improvement and development in order to achieve performance high levels. 40 adults, aged b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It is therefore necessary to educate the athlete in the conscious use of their will and respect for themselves and others (Di Onofrio et al, 2019;Woolf, 2020). Pedagogy therefore is a necessary component in doping…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore necessary to educate the athlete in the conscious use of their will and respect for themselves and others (Di Onofrio et al, 2019;Woolf, 2020). Pedagogy therefore is a necessary component in doping…”
Section: Discussionmentioning
confidence: 99%
“…Cohesion involves both individual and group components, respecting individual differences and/or potentialities and perceptions concerning the team's task and commitment to social unity (Carron et al, 1985;Horn et al, 2012). Cohesion is often identified as a simple relationship of friendship, but in a group, it is important to verify the orientation of the task in order to achieve a determined and inspiring goal shared by all team members (Di Onofrio et al, 2019). The findings of Prapavessis and Carron (1996) revealed that cohesion and anxiety were associated.…”
Section: Introductionmentioning
confidence: 99%